Exploring the Spiritual Formation of Generation Z Students in Christian Schools: A Reflective Journey - Amy Yoder, EdD (Journal of Scholarly Engagement)
This reflective narrative chronicles a transformative journey of an educator’s experience teaching in a private Christian school and the subsequent pursuit of research on the spiritual formation of Generation Z students. Drawing upon Dewey’s notion of reflection and a comprehensive review of the literature and spiritual development theories, the author examines why students in Christian schools identify teachers as the primary influence in their spiritual formation. This reflection explores the complexity of spiritual development, the challenges posed by Generation Z students’ digital native characteristics, and the feelings of inadequacy among teachers in fostering spiritual formation. Guided by Greenberger’s reflective framework and Dewey’s principle of continuity, the author aims to deepen her understanding of students’ perceptions and cultivate confidence and aptitude in supporting students’ spiritual growth. The analysis highlights teachers’ multifaceted roles as trusted confidants, mentors, role models, and spiritual guides, transcending the boundaries of academic instruction. The reflective practice findings emphasize the authenticity and modeling of faith by teachers and relationship building, which creates a powerful environment where students observe and internalize the practical application of Christian principles. Additionally, the study considers the varying stages of faith among students and the need for teachers to adapt their roles and approaches accordingly.